Ubicación óptima de reconectadores y fusibles en sistemas de distribución (2016)
In  this  article  a  methodology  to  resolve  the problem  of  optimal  location  of  reclosers  and fuses  in  power  electric  distribution  systems  is  presented,  to  improve  reliability  indices  associated  to  the  periodicity  of  the  transient  and  permanent  failures  in  the  distribution systems.  To  formulate  the  problem,  two  non-linear binary  mathematical  models  are  posed  that  consider the location of reclosers and fuses under two scenarios of  coordination, denominated  “fuse  save  scheme”  and  “fuse blow scheme”. The first model minimizes SAIFI index, and the second model minimizes MAIFI index. The set  of  constraints  is  the  same  for  both  models,  which considers  technical  and  operative  characteristics.  As solution strategy a methodology  is  proposed,  which considers  two  different  schemes  of  solution:  the  first scheme uses the commercial optimizer GAMS and the second  scheme  uses  as  solution technique  a  Chu  & Beasley genetic algorithm (CBGA). In order to verify the validity  of  both  strategies,  these  are  executed  in  two tests  systems  from  the  specialized  literature,  comparing the results obtained.